Where is the happiness in dementia? - Petty, Stephanie; Dening, Tom; Griffiths, Amanda; Coleston-Shields, Donna Maria (Cambridge University Press, 2016)
Our current research aims to explore how the emotional experiences of individuals with dementia are understood, and to improve the design and delivery of care interventions. A preliminary, incidental, finding from our initial systematic literature search is reported here. Increasingly, the experience of dementia is understood from the viewpoint of the individual. However, this is not reflected in the body of research literature, which is predominantly orientated towards detailing the neuropsychiatric symptoms of mood, cognition, behaviour or physiology and ‘managing’ the condition.